A Sensitive Aptamer-Based Biosensor for Electrochemical Quantification of PSA as a Specific Diagnostic Marker of Prostate Cancer - Shokoufeh Hassani; Armin Salek Maghsoudi; Milad Rezaei Akmal; Soheila Rahmani Rahmani; Pouria Sarihi; Mohammad Reza Ganjali; Parviz Norouzi; Mohammad Abdollahi (Frontiers Media S.A., 2020)
Purpose: The current project aimed to design a simple, highly sensitive, and economical label-free electrochemical aptasensor for determination of prostate-specific antigen (PSA), as the gold standard biomarker for prostate cancer diagnosis. The aptasensor was set up using a screen-printed carbon electrode (SPCE) modified by gold nanoparticles (Au NPs) conjugated to thiolated aptamers. Methods: Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were implemented for electrochemical (EC) characterization of the aptasensor. The determination of PSA was also performed through differential pulse voltammetry (DPV) in [Fe (CN) 6]3-/4- electrolyte solution. Results: The present aptasensor was shown an outstanding linear response in the concentration range of 1 pg/mL - 200 ng/mL with a remarkably lower limit of detection of 0.077 pg/mL. The optimum concentration for PSA separation and the optimum incubation time for antigen-aptamer binding were determined by observing and electing the highest electrochemical responses in a specified time or concentration. Conclusion: According to the results of the specificity tests, the designed aptasensor did not show any significant interactions with other analytes in real samples. Clinical functionality of the aptasensor was appraised in serum samples of healthy individuals and patients examining the PSA level through the fabricated aptasensor and the reference methods. Both methods are comparable in sensitivity. The present fabricated PSA aptasensor with substantial characteristics of ultra-sensitivity and cost-effectiveness can be conventionally built and used for the routine check-up of the men for prostate problems.